Narrative Function of Vladimir Propp in John Green’s Novel, The Fault in Our Stars - Dita Herma Yulistya Herma; Retno Budi Astuti (International Journal of English and Applied Linguistics (IJEAL), 2022)
Literature is defined as the work of feelings and expressions of human ideas that have a poetic form of writing which is presented or shared for everyone to read. A novel as one a literary work is prose in the form of books with narrative texts divided into several places and has many characters in there. Also, it can be researched because a novel has a story in form of narrative text. One of the novels is The Fault in Our Stars by John Green. The focus of this research was to know what are the 31 narrative functions by Vladimir Propp in The Fault in Our Stars novel. Hence the aim of this research is to find out the narrative functions in The Fault in Our Stars novel by John Green. This research, entitled Narrative Function of Vladimir Propp in John Green’s novel, The Fault in Our Stars uses a qualitative descriptive method to analyze the 31 narrative functions by Vladimir Propp. The results of this research indicate the 31 narrative functions by Vladimir Propp, there are 14 narrative functions in The Fault in Our Stars novels, such as interdiction, violation, delivery, villainy and lack, mediation, departure, the first function of the donor, receipt from a donor, struggle, branding, return, rescue, transfiguration, and wedding.